ANTI-METHICILLIN RESISTANT STAPHYLOCOCCUS AUREUS POTENTIAL OF PHYTOCHEMICALS IN TERMINALIA CATAPPA AND THEIR PROPOSED IN SILICO MECHANISM OF ACTION: Anti-MRSA potential of Terminalia catappa - LOKESH RAVI; DIVYA JINDAM; SUGANYA KUMARESAN; VENKATESH SELVARAJ; JAYARAMA REDDY (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study was to investigate the antibacterial potential of leaves of this Terminalia catappa and identify the mechanism of action for those phytochemicals present in this leaves. Methods: Phytochemicals were extracted using maceration and the extracts were analyzed using gas chromatography–mass spectrometry (GC-MS) to identify the chemical structure. Antibacterial potential was evaluated using agar well diffusion. The phytochemicals were subjected to in silico protein–ligand docking study to identify the mechanism of action. Results: In vitro antibacterial study demonstrated that the ethanol extract of the leaves has significant antibacterial activity against Staphylococcus aureus (SA) and methicillin-resistant SA (MRSA) with a zone of inhibition of 16 mm and 18 mm, respectively, at a concentration of 2 mg/ml. The chloroform and hexane extracts of the leaves did not demonstrate any significant activity. Based on GC-MS analysis and literature review, 12 phytochemicals were identified to be present in the ethanol extract of the T. catappa leaves. These molecules were subjected to in silico protein–ligand docking study against common drug target proteins of SA and MRSA. Among the studied ligands, granatin A demonstrated the highest significance to inhibit topoisomerase IV with a binding energy of −11.3 kcal/mol and produced 7 hydrogen bonds, followed by punicalin with −10.7 kcal/mol binding energy toward penicillin-binding protein 2a with 6 hydrogen bonds. Conclusion: Phytochemicals of T. catappa demonstrates significant drug ability potential against drug-resistant MRSA pathogen and demands further investigation on their individual activity and mechanism.